A preliminary assessment of the link between anxiety sensitivity cognitive concerns and suicidal thoughts through dissociative symptoms. Issue 1 (1st January 2022) - Caulfield, Nicole M.; Martin, Rachel L.; Smith, Nicole S.; Karnick, Aleksandr T.; Norr, Aaron M.; Capron, Daniel W.
ABSTRACT: Anxiety sensitivity (AS) and AS subfactors (physical, cognitive, and social) have been found to have robust associations with suicide risk. While the direct association between AS subfactors and suicide risk have been explored, little is known about how specific mechanisms, such as dissociation, might explain this relationship. This study aimed to run three analyses to examine the direct and indirect effects of suicidal thoughts and AS via dissociative symptoms. We predicted that dissociation would be a pathway through which AS physical concerns (ASPC) and AS cognitive concerns (ASCC) predicts suicidal ideation. Participants included 84 undergraduate students from a Southeastern University who were elevated on ASCC. Participants completed measures examining dissociative experiences, anxiety sensitivity, and current suicidal ideation. Results revealed that dissociation had a significant indirect effect with ASPC but not ASCC. The current preliminary study showed that ASCC had direct associations with suicide risk; however, those with lower levels of ASPC and dissociation may also be more likely to develop suicide risk. Future research should explore the possibility that the dissociation/ASPC and ASCC pathways are separate, but related, paths to suicidality.